The Relationship Between Intrapersonal Intelligence and Learning Independence of Students - Misbakhul Jannah (Altruistik : Jurnal Konseling dan Psikologi Pendidikan, 2022)
This study aims to determine the level of intrapersonal intelligence, independence of learning, and the relationship between intrapersonal intelligence and learning independence of students. The approach in this study uses a quantitative approach with descriptive and correlational research types. The object of the research is 144 students of class XI, determined by the Slovin formula from a population of 223 students. The instrument used is intrapersonal intelligence scale and independence of learning scale. This study uses descriptive statistical analysis techniques and correlational analysis. The results showed that the dominant student's intrapersonal intelligence was in the high category with a percentage of 72%, and the student's learning independence was relatively in the medium category with a percentage of 56.25%. While the relationship between intrapersonal intelligence and learning independence of students shows a correlation value of 0.062, meaning that there is no relationship between intrapersonal intelligence and independence of learning.